2012
DOI: 10.1108/09564231211226097
|View full text |Cite
|
Sign up to set email alerts
|

Waiting for service at the checkout

Abstract: PurposeIn retail settings, customer satisfaction is generally associated with a global evaluation of the store, i.e. the store image. Waiting for service is not part of the store image dimensions, but it does play an increasingly important role in the retail experience where waits are often inevitable. The present study seeeks to investigate how waiting for service at the checkout counter influences overall satisfaction, along with the store image.Design/methodology/approachThe study combines services marketin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(20 citation statements)
references
References 113 publications
(154 reference statements)
0
19
0
1
Order By: Relevance
“…Although such anxiety-related time distortion has been thought to be an evolutionary basis that facilitates adaptive responses to environmental stimuli (Matthews and Meck, 2014;Lake et al, 2016), in some situations, an anxious individual might not desire such time distortion. For example, previous studies have found that prolonged waiting of time can lead to anxiety (Dasu and Rao, 2009;Van Riel et al, 2012), which in turn leads to irrational decision-making behaviors (Rajamma et al, 2009;Aniae et al, 2011). Therefore, methods of reducing anxiety-related time overestimation are required.…”
Section: Introductionmentioning
confidence: 99%
“…Although such anxiety-related time distortion has been thought to be an evolutionary basis that facilitates adaptive responses to environmental stimuli (Matthews and Meck, 2014;Lake et al, 2016), in some situations, an anxious individual might not desire such time distortion. For example, previous studies have found that prolonged waiting of time can lead to anxiety (Dasu and Rao, 2009;Van Riel et al, 2012), which in turn leads to irrational decision-making behaviors (Rajamma et al, 2009;Aniae et al, 2011). Therefore, methods of reducing anxiety-related time overestimation are required.…”
Section: Introductionmentioning
confidence: 99%
“…Customers recognize that the store usually provides information and know-how the store handles complaints. The convenience of shopping is an important aspect, and the shopping experience facilities can have an inappropriate influence on customers' perceptions of the store [30]. Completeness of shopping aids, such as; adequate packaging/wrapping and shopping baskets and additional lines and waiting times related to customers leaving the store, become experiences for the customers [31].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Van Riel et al (2012) argued that waiting is integral to the service experience in the service industry where customers have to be there in person. According to Tom and Lucey (1995), waiting is an activity that customers find undesirable but need to engage to get their service rendered.…”
Section: Waiting Timementioning
confidence: 99%